PAPR Reduction Techniques in Generalized Inverse Discrete Fourier Transform Non-Orthogonal Frequency Division Multiplexing System - Iram Maisarah Mokhtar; Norulhusna Ahmad; Hazilah Mad Kaidi; Mohd Azri Mohd Izhar; Norliza Mohamed (Institute of Advanced Engineering and Science, 2018)
A promising system of Generalized Inverse Discrete Fourier Transform Non-Orthogonal Frequency Division Multiplexing (GIDFT n-OFDM) system can fulfil the requirement of supporting higher data rate in Fifth Generation (5G) technology. However, this system experience High Peak to Average Power Ratio (PAPR) due to massive number of subcarriers signal is transmitted. In this paper, three types of usual PAPR reduction techniques were applied in GIDFT n-OFDM system which are Clipping, Partial transmit Transform (PTS) and Selective Mapping (SLM). The system performance is compared and evaluated using Complementary Cumulative Distribution Function (CCDF) plot. Simulation results show that SLM technique give significant reduction of PAPR 9 dB of the original performance.